2018
DOI: 10.18229/kocatepetip.419014
|View full text |Cite
|
Sign up to set email alerts
|

Afyon Kocatepe Üni̇versi̇tesi̇’nde Meme Kanseri̇ Tanisi İle Taki̇p Edi̇lmekte Olan Hastalarda Tamamlayici Ve Alternati̇f Tedavi̇ Kullanimi

Abstract: ÖZ AMAÇ: Bu çalışmada Afyon Kocatepe Üniversitesi'nde meme kanseri nedeniyle takip edilmekte olan hastalarda tamamlayıcı ve alternatif tedavi (TAT) kullanım sıklığının ve TAT ile ilgili uygulamaların belirlenmesi ve incelenmesi amaçlanmıştır. GEREÇ VE YÖNTEM: Çalışmamıza Afyon Kocatepe Üniversitesi Tıp Fakültesi Hastanesi, Tıbbi Onkoloji Polikliniği ile Fizik Tedavi ve Rehabilitasyon Ana Bilim Dalı'na başvuran toplam 70 meme kanserli hasta dahil edilmiştir. Hastaların sosoyodemografik özellikleri ile, kullanıl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
2
6
0
8
Order By: Relevance
“…It was determined that the CT method most commonly preferred by breast cancer patients was natural products. Among Turkish cancer patients, natural products are the most commonly used CT method and the rate of use varies between 30-98% 8,9,15,22 . The reason why Turkish patients mostly prefer natural products (herbs, vitamins and minerals) is the ease of use of non-prescription drugs 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was determined that the CT method most commonly preferred by breast cancer patients was natural products. Among Turkish cancer patients, natural products are the most commonly used CT method and the rate of use varies between 30-98% 8,9,15,22 . The reason why Turkish patients mostly prefer natural products (herbs, vitamins and minerals) is the ease of use of non-prescription drugs 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Turkey and the world have found that the use of CT is quite common among breast cancer patients [7][8][9] . These patients may refer to CT for reasons such as eliminating disease symptoms, reducing the side effects of cancer treatment modalities, strengthening the immune system, and improving emotional well-being 8,[10][11][12] . NCCIH has classified complementary health practices under three headings: Natural products, mind and body practices, and other complementary health approaches 5 .…”
Section: The National Center For Complementary Andmentioning
confidence: 99%
See 1 more Smart Citation
“…TSY kullanan hastaların %44.3'ü tanı aldıktan hemen sonra tedavi süreci başlamadan bu yöntemlere başvurduğunu ifade ederken, %35.7'si ise halen kanser tedavisi devam ederken TSY'a başvurduğunu belirtmiştir. 9 Öztürk ve ark. jinekolojik kanserli hastaların TSY kullanımını %28,0 olarak belirlenmiştir.…”
Section: Verlerin İstatstistiksel Analiziunclassified
“…20 Düzen ve Korkmaz çalışmalarında, hastaların %63,6'sının doktoru ve %81,8'inin hemşiresi ile paylaşmadığını bulmuştur. 9 Nazik ve ark. 'nın çalışmalarında, jinekolojik kanserli hastaların %56,1'inin TSY kullandığını hemşiresi ile paylaştığı saptanmıştır.…”
Section: Araştırmanın Etik Yönüunclassified